The development of youth creativity based on local wisdom in Surakarta / Figur Rahman Fuad and Adam Wahida - Fuad, Figur Rahman; Wahida, Adam (Faculty of Art and Design, 2019)
This paper is based on the mapping of the youngsters and environment potential at Joyoraharjan, Surakarta. These traditional art-based potentials are developed in the participatory design to gain new perspective on interpreting the local wisdom. The method used is under research and development (R&D) design with the following stages: 1) research and information collecting, 2) planning, 3) preliminary product development, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing, 9) final product revision and 10) dissemination and implementation. The data was collected through in-depth interview, participatory observation, document analysis and focus group discussion. The data is displayed in qualitative descriptive and the correlation among the variables will be analyzed using the interactive model of analysis.